Student perceptions of the use of PechaKucha presentations in Spanish as a foreign language - González Ruiz, Cristina (2020)
Developing student’s ability to communicate in the target language is the primary aim of foreign language teaching. Nowadays, information technology resources, such as videos or PowerPoint presentations, are offering platforms where language students can safely and creatively develop their oral communication in the target language while developing their presentation skills (Tomsett and Shaw, 2014; Shiobara, 2015). In particular, this pilot study explores the use of the digital presentation format PechaKucha 20x20 as a learning tool for oral communication in a Spanish as a Foreign Language (SFL) course. Its format consists of 20 slides that automatically run for 20 seconds each, which means that the entire presentation only lasts 6 minutes and 40 seconds. Two questionnaires, as presenter and as audience, were administered to intermediate Spanish students to explore their perceptions of the use of this presentation format. In general, students show positive views and attitudes towards the use of the PechaKucha format. Although students reported to enjoy creating and presenting using this format, time constraints and lack of flexibility were reported as drawbacks. Results of the study and implications of PechaKucha in the language classroom will be discussed.